ESPECTROFOTOMETRIA APLICADA NA ANÁLISE DE NANOCARREADORES LIPÍDICOS CONTENDO ATIVOS PARA LIPODISTROFIA GINOIDE - Baldisserta, Denise Bom (2014)
Gynoid lipodystrophy (GLD), also known as cellulite, is a common dermatological condition among women after the puberty, mainly concentrated in the pelvic region, lower limbs and abdomen. It´s a tissue edematous infiltration that promotes unattractive changes, the skin becomes to have a paddled aspect or “orange peel”, conducing to a low self esteem. The exactly etiology of GLD is unknown, however, its presence and level are related to several factors like genetic, emotional, metabolic and hormonal, besides the age, sex, blood pressure, obesity and habits like smoke, sedentary, tight clothes and poor diet. There are many ways to treat this condition, being the most used and easy accessed the use of cosmetic products having as active principles the vasopressure action, anti-inflammatory, lower microcirculation and lipolytic agents. In the present work, methods for analysis of the lipid nanocarrier containg actives employees for GLD treatment (diidromiricetin, diosgenin and synephrine) were developed and validated. There aren’t decrypted monographs in pharmacopeias to analyze these substances in pharmaceutical formulas. In the spectrophotometric method UV-VIS the diosgenin and the dihydromyricetin were quantified in 434 nm and 561 nm, respectively, used as reagents sulfuric acid and ρ- anisaldehyde. Synephrine can be quantified by the derivative ultraviolet spectrophotometry, 239 nm wave-length, in the second order, medium scan, Δλ 10.000 and scale factor of 50, using ethanol as a solvent. The methods showed to be specific, linear, precise, exact and robust to the actives quantification. It can be concluded that the validated methods were of easy execution, fast and with a low cost, to do the quality control analyses.